Niemieckie composita jako jednostki słowotwórcze nacechowane kulturowo w przekładzie na język polski - Altmann, Jakob (Przekłady Literatur Słowiańskich, 2016)
German compound words as culturally marked word‑formation units and their translation into Polish This article deals with the topic of German compound words as culturally marked word‑formation units and their translation into Polish, based on the example of the translation of Herta Müller’s novel Herztier (The Land of Green Plums). Firstly, the author specifies compound words as such — in German and Polish, as well as their differing functions and types. Under focus especially are the divergences in the area of the terms used in each language (cf. Zusammenrückung vs. zestawienie and zrost). In the beginning of the practical part, which is dedicated to an analysis of the translation into Polish, the attention of the reader is directed to the potentially problematic characteristics of Herta Müller’s prose, which can appear during the process of translation. In this regard, we can state: that the typical German compound words cannot be translated into Polish without semantic displacements, for the translation it is necessary to use partly uni‑ and partly multi‑verbated constructions. However, this results in the loss of an important degree of imagery. Many of these compound words are culturally marked collocations, e.g. Patentstrümpfe or Essenskarte, which cannot be translated faithfully into Polish. Nevertheless, one can say that the translator has found satisfactory translational solutions, which we can partially explain as parallels between the cultural experiences of Herta Müller (her life in the Romanian People’s Republic) and of the translator, Alicja Buras (raised in the Polish People’s Republic). All in all, we can recognise in the Polish translation the clear effort to find the golden mean between the so‑called covert translation and overt translation, with the second one dominating. Key words: compound words, Polish‑German translation, word formation, The Land of Green Plums, cultural imprint